2020
DOI: 10.1136/bmjopen-2020-042573
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognosis for COVID-19-induced acute kidney injury: a meta-analysis

Abstract: ObjectiveTo analyse the incidence, risk factors and impact of acute kidney injury (AKI) on the prognosis of patients with COVID-19.DesignMeta-analysis.Data sourcesPubMed, Embase, CNKI and MedRxiv of Systematic Reviews from 1 January 2020 to 15 May 2020.Study selectionStudies examining the following demographics and outcomes were included: patients’ age; sex; incidence of and risk factors for AKI and their impact on prognosis; COVID-19 disease type and incidence of continuous renal replacement therapy (CRRT) ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
106
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 33 publications
17
106
1
14
Order By: Relevance
“…We found that the incidence of AKI in COVID-19 patients was 10%. A similar AKI incidence in COVID-19 patients (10.8%) was also reported in other studies [34]. The diversity of patients included in our systemic review caused heterogeneity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that the incidence of AKI in COVID-19 patients was 10%. A similar AKI incidence in COVID-19 patients (10.8%) was also reported in other studies [34]. The diversity of patients included in our systemic review caused heterogeneity.…”
Section: Discussionsupporting
confidence: 85%
“…SARS-CoV-2 enters cells via the angiotensin-converting enzyme 2 (ACE2) receptor and is highly homologous to SARS-CoV [33]. High ACE2 expression in proximal tubular epithelial cells may be a potential target for kidney injury [34]. Renal abnormalities, such as proteinuria, haematuria, and AKI, occur in patients with COVID-19 [35].…”
Section: Discussionmentioning
confidence: 99%
“…Se han descrito alteraciones renales frecuentes en COVID-19, manifestándose principalmente con insuficiencia renal, con una etiología habitualmente multifactorial que incluye la propia afectación por el virus, el cuadro inflamatorio sistémico y las alteraciones de la coagulación y en algunos casos secundarias a rabdomiólisis 3 , 6 , 49 , y que se asocian con mayor gravedad y mortalidad de la infección 50 .…”
Section: Manifestaciones Renales Y Genitourinariasunclassified
“…Recent data proposed several demographic parameters—such as male sex, older age, diabetes mellitus, hypertension, cardiovascular disease, congestive heart failure, high body mass index, chronic kidney disease (CKD), genetic risk factors, immunosuppression, and smoking history—that could induce or increase the incidence and progression of AKI [ 10 , 40 , 41 , 42 ]. Lin et al performed the first systematic analysis of the COVID-19 risk factors on 79 research articles, and showed that patients with advanced age were more vulnerable to the development of AKI, probably due to weakened immune system function and the physiological aging of organs [ 43 ]. Moreover, Shastri et al observed that male patients had a lower capacity in SARS-CoV-2 clearance after infection compared to female patients, underlying the gender disparity in the disease’s severity [ 44 ].…”
Section: Kidney Dysfunction In Sars-cov-2 Infection and The Risk Fmentioning
confidence: 99%
“…Moreover, Shastri et al observed that male patients had a lower capacity in SARS-CoV-2 clearance after infection compared to female patients, underlying the gender disparity in the disease’s severity [ 44 ]. Moreover, the impact of high-risk behaviors like smoking and alcohol consumption could make male patients more susceptible to AKI in COVID-19 disease [ 43 ]. Moreover, certain genetic traits might increase susceptibility to the development of AKI in the course of SARS-CoV-2 infection [ 10 ].…”
Section: Kidney Dysfunction In Sars-cov-2 Infection and The Risk Fmentioning
confidence: 99%